2022
DOI: 10.3847/1538-4357/ac9184
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Elastic Strain toward Crustal Fracture in Magnetized Neutron Stars

Abstract: This study investigates elastic deformation driven by the Hall drift in a magnetized neutron-star crust. Although the dynamic equilibrium initially holds without elastic displacement, the magnetic-field evolution changes the Lorentz force over a secular timescale, which inevitably causes the elastic deformation to settle in a new force balance. Accordingly, elastic energy is accumulated, and the crust is eventually fractured beyond a particular threshold. We assume that the magnetic field is axially symmetric,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…where the radial functions x l and k l (l = 1, 3) are determined using Equations ( 24) and ( 25) (Kojima et al 2022);…”
Section: Quasi-stationary Elastic Responsementioning
confidence: 99%
See 1 more Smart Citation
“…where the radial functions x l and k l (l = 1, 3) are determined using Equations ( 24) and ( 25) (Kojima et al 2022);…”
Section: Quasi-stationary Elastic Responsementioning
confidence: 99%
“…The Lorentz force is comparable in magnitude to the elastic force in the crust. However, only static magneto-elastic equilibria of the crust have been studied thus far (Kojima et al 2021(Kojima et al , 2022Fujisawa et al 2023). These studies demonstrated that neutron star models with strong magnetic fields are possible owing to the elasticity of the crust.…”
Section: Introductionmentioning
confidence: 99%